Genre(less) and purpose(less): Online news galleries. (December 2017) - Caple, Helen; Knox, John S.
Highlights: Online news galleries are an example of the new storytelling practices in online media, but new and emerging genres in online galleries are limited. Two genres in online galleries - unfolding stories and bios - are identified and described. Episodic galleries are identified as having the potential to emerge as a genre. Social factors related to online news are more important than technological factors in the emergence of new news genres. Abstract: Online news galleries are an example of the new storytelling practices in online media. They draw on existing practices of news reporting (e.g. employing news images with headlines, captions, and sometimes leads), yet offer new possibilities due to their unique features, which allow for large numbers of images of a single event to be published, and to be the featured medium of a given story. The combination of a new social context for the exchange of meanings and new potential for storytelling would suggest that online news galleries could be expected to be a location for the emergence of new genres. However, 'new' or 'emerging' genres in online news galleries are limited. This is due to a combination of factors, including the economic/commercial environment in which online newspapers operate, and the institutional practices by which galleries are produced. Drawing on datasets collected in 2009 and 2013, we identify and describe two genres, and one potentially emerging genre. Variations on some familiar genres do appear to be emerging in published online news galleries. The extent to which novel genres will emerge over time will depend on developments in the media landscape, and on the adaptability of the mass media institutions that author and publish them.